Magnetic properties for magnetic transducer - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
Knowing the basic terminology for describing magnetic effects and properties are essential since magnetic materials can be used in inductive sensors as in the form of core. The various types of magnetic behaviour and properties of hard and soft magnetic materials (used in inductive sensor) need to be identified in order to decide on the appropriate applications in biomedical and industrial field